Hitsville [compact disc] : the making of Motown : original motion picture soundtrack. - Reeves, Martha; Gaye, Marvin; Terrell, Tammi; Wonder, Stevie; Strong, Barrett; Walker, Jr; Wells, Mary, 1943-1992; Robinson, Smokey, 1940-; Ruffin, Jimmy (Motown Records, 2019)
Original motion picture soundtrack from the Showtime documentary film.